Behavioral change in waste separation at source in an international community: An application of the theory of planned behavior. (November 2021) - Hu, Jiarong; Tang, Kelvin; Qian, Xuepeng; Sun, Furong; Zhou, Weisheng
Highlights: Survey is adopted to capture the change of the constructs before and after. The selected community provides a novel observation of behavior change. Intention structure was concluded based on Theory of Planned Behavior. Environmental knowledge and rules in the community are important factors. Abstract: Analysing and understanding the factors that influence the behavior of waste separation is critical to improved waste management. This study identified the factors behind behavioral change in waste separation at source in an international community. The theory of planned Behavior (TPB) was adopted to conduct a self-report questionnaire survey twice, in which 354 residents participated at Time1 and 331 at Time 2, with a retention rate of 93.5%. The questionnaires were designed based on TPB with additional questions regarding waste separation rules in the community, experience of waste separation, and environmental knowledge. With the questionnaire data and follow-up qualitative interviews, factors related to waste separation through factor analysis and structural equation modelling and text mining were specified. The panel data collected over three months demonstrated the changes in attitudes, subjective norms, and perceived behavioral control that affect behavioral intention in the process of behavior adaption. Combined with interview data, the reasons for these changes can be further attributed to individuals' environmental knowledge and community guidelines. The findings imply that policies targeting environmental education and rulemaking are effective to help residents form more positive intentions towards waste separation.